High-performance pull-in time accelerometer - Dias, Rosana Maria Alves (2015)
A closed-loop accelerometer based on electrostatic pull-in time is presented here. The main goal is to achieve high-performance, namely in respect to noise and sensitivity, with a very simple readout mechanism. An integrated system was implemented comprising actuation and readout circuitry, FPGA and MEMS sensor. It presents a good performance in comparison to the state-of-the-art. Experimental measurements have shown a sensitivity of 61.3 V-2/g, dynamic range of 110 dB and a noise level set below 3 mu g/root Hz, by the mechanical-thermal noise only. The measured bias stability is better than +/- 250 mu g over 48h with temperature control of +/- 1 degrees C.